Patient´s prognostic understanding starts with physician´s prognostic awareness (Paliativní medicína, 2022)
AbstractPrognostication and prognostic conversations represent one of the main challenges in oncological haematology. This process fundamentally shapes patient’s prognostic awareness. Trajectory of illness in patients with haematological malignancies has significantly changes due to modern therapies in past few years. For treating haematologist, prognostication is difficult in therapy of both adult and pediatric patients. Early integration of palliative care team may help with patient´s prognostic understanding and can facilitate difficult discussions with the patient and family. The article introduces basic principles of prognostic conversations in literature and authors´ experience from palliative care teams in General Faculty Hospital and University Hospital Motol in Prague.Key words: prognosis, haematological malignancies, prognostic awareness, palliative care